An Analysis of Student Errors in Solving Problems in Basic Computer Programming Using Matlab - Murniasih, Tatik Retno; Fayeldi, Trija (Study Program of Mathematics Education University of Muhammadiyah Malang, 2018)
The aim of this research is to find out students‘ errors and the factors which cause students to make errors when they solve problems in Basic ComputerProgramming using Matlab. The methods used to collect the data aredocumentation, test, and interview. This is a qualitative and uses descriptive method. The subject of this research is 35 students of Mathe-matics Education Departement class of 2015B. Three students with low ability who made errors in their worksheet are chosen as the interview subject. The data validation test is conducted with triangulation technique. The result is that the students‘ errors are divided into three categories, i.e: the errors in understanding the concept, the procedure, and the final result. Based on the result of this research, it is concluded that 17.1% of the students made errors in understanding the concept, 46, 7% of the students made errors in the procedure, and 5, 7% made errors in the final result. The factors influencing the students‘ errors are lack of understanding in prerequisite materials and lack of practice in solving Basic Computer Programming problems.